PENGARUH MEDIA SOSIAL DAN LINGKUNGAN SOSIAL SEKOLAH TERHADAP PERILAKU RELIGIUS SISWA - Rojak; Saifuddin Zuhri; Junaedi Sastradiharja (Balai Diklat Keagamaan Jakarta, 2021)
This study aims to describe the influence of media and school social environment on students' religious behavior separately or simultaneously. This used a survey method with a correlational and regressive approach. The sample was 108 from 144 students of class XI Madrasah Aliyah Negeri 17 Jakarta in the odd semester of the 2020/2021 school year. The data was collected using a questionnaire and observation. The type of analysis used is correlation and regression. The research results are: First, there is a positive and significant influence of social media on students' religious behavior. It can be read that an increase will follow every 1-point increase in social media (X1) in students' religious behavior (Y) of 0.228 points. Second, there is a positive and significant influence of the school social environment on students' religious behavior with a coefficient r of 0.358 and a coefficient of determination (R2) of 12.8%. The regression equation Ŷ = 88.429 + 0.156 X2. It means that an increase will follow every 1-point increase in the school social environment (X2) in students' religious behavior (Y) of 0.156 points. Third, there is a positive and significant influence on social media and the school social environment simultaneously on students' religious behavior. It means that every 1-point increase in social media (X1) and the school social environment (X2) together will be followed by an increase in students' religious behavior (Y) of 0.384 points.